A qualitative analysis of nonoffending partners’ experiences and perceptions following a psychoeducational group intervention - Cahalane, Hilary; Duff, Simon (Taylor & Francis, 2017)
The present research is a qualitative study analysing therapeutic letters written by the nonoffending partners of men who have perpetrated child sexual abuse, after completion of a psychoeducational group intervention. It sought to identify themes relating to their experiences post-intervention. Findings indicated that the intervention contributed to women having increased insight into sexual offending, and feeling more confident and empowered. In addition, they displayed an awareness of risk issues, and an intention to play a role in helping to manage their partner’s future risk. Implications for research and clinical practice are discussed.